Assessment Of Sedimentation Process At Kenyir Dam River Using Hydraulic - Kamarudin, Ahmad Afif (Universiti Sains Malaysia, 2021)
The dam is a multi-function device, not only provides flood mitigation and water activities but also generates electricity through turbine operation. However, the flowing water discharge from turbine operation can have an impact on the downstream area. This research presents the study of flow characteristics of turbine operation at Kenyir Dam and to determine the possibility of sedimentation at the downstream during the operation of the turbine. This physical model of Kenyir Dam built by the scale of 1:50 is the replication of the real site with the using of granite to produce the exact result to the real condition. Through intensive observation, the flow characteristics and the possibility of sedimentation at downstream area during turbine operation are determined. The relationship between velocity profile, the ground contour and the flow pattern has determined the location of sedimentation. This research conducts with two cases study of the operation of the turbine with 5 l/s, 10 l/s and 15 l/s and its combine operation of spillway with 100 l/s. The flow characteristic depends on the amount of water discharge. Therefore, the sedimentation in the downstream area can be expected. In this study, the sedimentation happens when the velocity of the water is slowing down into the range of settling velocity, thus the transportation of the sediment particle is considered to be deposit in that area. The velocity for the deposition of sediment is 0 to 4 cm/s after ratioed to the model velocity. This study shows the sedimentation is based on ground contour pattern and the water discharge from the dam.